Researching How AI Works Marketing Influence Trust Consumers In Two Culture Different - Elsa Islammia Pasha (Journal of Strategic Marketing and Applied Economics, 2025)
Development rapidly intelligence artificial intelligence (AI) in digital marketing strategy has bring up challenge new in understand dynamics trust consumer cross culture . In an increasingly global context connected , important For evaluate How perception consumer to use of AI in marketing different between culture , especially related with aspect privacy , personalization , and transparency . Article This aim For research influence use of AI in marketing to trust consumers in two culture different , namely culture individualistic ( United States ) and culture collectivism (Indonesia). Research This use approach quantitative with method survey , involving 400 respondents who were divided equally between the two countries . The instruments used is questionnaire closed with Likert scale for measure perception trust , AI transparency , and value culture consumers . Data analysis was carried out using Structural Equation Modeling (SEM) to test connection between variables . The results show that AI in marketing own influence positive to trust consumers , however mediated in a way significant by value culture . Consumers in culture individualistic more value personalization and data control , while consumers in culture collectivistic more influenced by opinion social and trust institutional findings​ This give outlook important for global companies for adjust marketing strategy AI -based according to with context target culture .​